Proposals of solution for the apparent legal conflict that may arise between the right to life of the unborn and the rights of the mother - Iñiguez Manso, Andrea Rosario; Peredo Rojas, Marcela Inés (Derecho Público Iberoamericano, 2020)
Article 19 N° 1 parr. 1 of the Constitution recognizes to every person the right to life and it´s physical and psychological integrity. It also declares in parr. 2 that protects the life of the unborn. Therefore, the Constitution shelters the life of the unborn and the mother. The problem is to determine how could our legal system react when there is an apparent conflict between the rights of the mother and the baby. Our investigation tries to give some criterions to solve this issue.